VD_FINDINFO HC / 2013 / 520 vom 30. Juli 2013 - VD Tribunal cantonal (2013)
SALAIRE, CLASSE DE TRAITEMENT, EMPLOYÉ PUBLIC | 46 al. 2 LFPr, 23 LPers-VD, 24 LPers-VD, 46 al. 2 OFPr, 6 al. 1 RSRC, 6 al. 2 RSRC